PATTERN OF BURNS AT LADY READING HOSPITAL, PESHAWAR - Aslam, Muhammad; Niazi, Muhammad Zarar; Mustafa, Ghulam (Journal of Postgraduate Medical Institute, 2012)
Objective: To describe the pattern of burn in Plastic Surgery and Burn Unit Lady Reading Hospital. Methodology: This one year (January 2009 to December 2009) descriptive study was carried out at Plasticsurgery and Burn Unit Lady Reading Hospital, Peshawar. Manual and computerized data comprisingepidemiological variables of all the patients presenting with acute burn was recorded. Results wereanalyzed with SPSS 15. Results: During one year study period, 758 patients were included. Male to female ratio was 1.5: 1. Meanage was 13.59 years (Std. deviation 14.162). Median age was 7 years. Mean Total Body Surface Area(TBSA) burn was 14.53 %. Home was the site of accident in most cases (88.1 %). There was no statisticalsignificance in gender and percentage of burn area (p value: 0.363). Scald and flame burn were the causeof burn in 91.2 % of the cases. 519 (68.5%) of the patients were from Peshawar district. Majority of burnvictims (59.2%) were below 10 year of age. Conclusion: Majority of burn accidents occur at home and are preventable. Scald injury is the mostcommon cause of burn resulting in two third of the total burns. Majority of the patients are children.